Upaya Kepala Sekolah dalam Meningkatkan Kualitas Standar Proses Pembelajaran di SMA Negeri 1 Gabus - Weny Erawati; Zaki Afifi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the principal's efforts to improve the quality of the learning process at SMA Negeri 1 Gabus, identify supporting and inhibiting factors, and describe the strategies used to improve learning quality. This study employed a qualitative approach with field research designed as a case study and supported by a phenomenological perspective. Data were collected through interviews with the principal, vice principal for curriculum, and teachers; observations of academic supervision and classroom learning processes; and documentation studies of the School Work Plan, academic supervision program, and other learning documents. Data validity was tested through triangulation of sources and techniques, while data analysis was conducted inductively following the interactive model of Miles, Huberman, and Saldaña. The results indicate that the principal carries out his role as a learning leader through four main efforts: participatory work program planning, implementation of coaching-oriented academic supervision, continuous teacher competency development, and consistent monitoring and evaluation of learning. The success of these efforts is supported by the commitment of the principal, the cooperation of the school community, and adequate infrastructure, although obstacles such as gaps in teachers' technological competencies and rapid changes in education policy remain. This study concludes that improving the quality of learning process standards is the result of synergy between effective instructional leadership and the shared commitment of all school members to maintaining educational quality.